Corporate demand for general takāful in Malaysia - Hamim Syahrum Ahmad Mokhtar; Izwayu Abdul Aziz; Noraziyah Md Hilal (ISRA International Journal of Islamic Finance, 2017)
Purpose: This study on corporate demand for general takāful (Islamic insurance) aims to identify potential growth areas and areas for improvement in takāful business practices in Malaysia. Design/methodology/approach A survey on corporates' protection needs, takāful/insurance coverage obtained and awareness on takāful/insurance was conducted for this paper. Findings The findings from the survey are as follows: There is potential for takāful operators to further penetrate the corporate sector, as the majority of respondents indicated willingness to spend on takāful/insurance. Emphasis on takāful value propositions apart from its Sharīʿah compliance status is needed to attract corporates, as respondents were found to be indifferent on Sharīʿah compliance status of their protection. Strong market presence, expanded product offerings and efficient services were key determinants to attract takāful subscription. Respondents' heavy reliance on intermediaries warrants strong collaboration with intermediaries to widen market outreach. The small and medium enterprises segment appeared promising, as it is found to be underserved despite having higher propensity to obtain takāful/insurance coverage compared to the overall respondents. Research limitations/implications This study is limited to Malaysia's experience. The findings are indicative (though they may not be conclusive) of the target segment as well as the takāful industry as a whole. Originality/value The insights on respondents' considerations when obtaining takāful/insurance coverage and the correlation of these factors with respondents' characteristics can assist takāful/insurance providers in structuring products and business strategies to better serve this market segment. The paper may also aid discussions among researchers and regulators on areas for further development of the industry.
Keywords: 330; business entities; corporate; general takāful; Insurance